Numerical modeling of the dynamics of the clutch couplers - D. V. Shevchenko; M. A. Kudryavtsev; A. M. Orlova; S. A. Ponomarev; A. M. Sokolov; Yu. V. Savushkina (Вестник Научно-исследовательского института железнодорожного транспорта, 2019)
One of the priorities of the program “Strategy for the development of railway transport in the Russian Federation until 2030” is the introduction and development of heavy haul traffic, allowing to ensure the increasing volume of freight traffic and significantly improve the efficiency of railways. Main challenges for scientific research and design development to ensure the creation of freight cars for heavy haul traffic, along with an increase in longterm load and decrease in tare weight, include the issue of increasing the load from the wheelset to the rails to 27 tons for heavy haul cars SA-3T and couplers SA-3. It is shown that increasing the load from the wheelset to the rails up to 27 tons while maintaining the dynamic running load within the normalized values can be achieved by increasing calculated deflection of the spring suspension of the truck, which in turn leads to an increase in the possible height difference between the couplings of adjacent cars. Authors explain necessity of putting into operation a coupler for heavy haul cars SA-3T, providing an increase in the vertical coupler contour line up to 210 mm. Regulatory documents governing the provisions of automatic coupling devices in freight cars were analyzed. Dynamic computational models have been developed that describe the behavior of automatic couplings in the process of coupling cars, taking into account the inertial characteristics of all parts included in the assembly, the geometric nonlinearity associated with their contact interaction, and the elastic-damping properties of the absorbing device. Verification of calculated dynamic model has been carried out. Numerical experiments simulating the coupling of the considered automatic coupling devices with the most unfavorable possible combinations of horizontal deviations and rotation angles were performed. It is confirmed that the developed design of the coupler CA-3T provides grip when there is a possible difference between the lower surfaces of the locks of adjacent coupler up to 210 mm both between themselves and with the typical coupler CA-3.